LudoBites : recipes and stories from the pop-up restaurants of Ludo Lefebvre - Lefebvre, Ludovic (Ecco, 2012)
Details the author's journey overseeing a touring restaurant that roved the streets of Los Angeles, sharing the story of his success and providing recipes for new and inventive ways of cooking.